2006
DOI: 10.1186/1476-7120-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Differing myocardial response to a single session of hemodialysis in end-stage renal disease with and without type 2 diabetes mellitus and coronary artery disease

Abstract: BackgroundThough hemodialysis (HD) acutely improves cardiac function, the impact of background diseases like coronary artery disease (CAD) and Type 2 diabetes (DM) in the setting of end-stage renal disease (ESRD) is not known. Tissue velocity echocardiography (TVE) offers a fast choice to follow changes in myocardial function after HD in ESRD with concomitant DM and /or CAD.Methods46 subjects (17 with ESRD, Group 1; 15 with DM, Group 2; 14 with DM+CAD, Group 3) underwent standard and TVE prior to and shortly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…E/Em ratio is a reliable marker of increased LV filling pressure in a general cardiac population in those with LVsystolic dysfunction. Recently, a study in predialysis patients with moderate to severe chronic renal failure (stages [3][4][5] showed that CKD severity alone was positively associated with elevated LV filling pressure assessed by E/Em ratio [25]. Contrary to that we found that E/Em increases the predictive power in dialysis group.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…E/Em ratio is a reliable marker of increased LV filling pressure in a general cardiac population in those with LVsystolic dysfunction. Recently, a study in predialysis patients with moderate to severe chronic renal failure (stages [3][4][5] showed that CKD severity alone was positively associated with elevated LV filling pressure assessed by E/Em ratio [25]. Contrary to that we found that E/Em increases the predictive power in dialysis group.…”
Section: Discussioncontrasting
confidence: 70%
“…Majority of the studies have demonstrated the association of CKD to strain deformation parameters. Mainly global longitudinal strain (GLS) was significantly related with the decline of renal function [4][5][6][7][8]. Only a few stud- 1 3 ies evaluated the prognostic value of GLS in patients with CKD in different stages of chronic renal failure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the previous study was relatively small. 25 To our knowledge, the present study is the first to use pulsed-wave TDI to directly compare echocardiographic differences between ESRD patients with type 2 DM and those without DM on maintenance hemodialysis in a relatively large cohort study. Interestingly, ESRD patients with DM had a more pronounced diastolic dysfunction than the non-DM group, as evidenced by a significantly lower e' and higher E/e', regardless of the LV mass.…”
Section: Discussionmentioning
confidence: 99%
“…Measured variables were isovolumic contraction times (IVCT) and velocities, isovolumic relaxation times (IVRT), ejection times (ET, defined by the period between aortic valve opening and closure), peak systolic velocities, early (E′) and late (A′) diastolic velocities and filling times (summation of early and late diastolic filling times) were calculated from the tissue velocity profile (Govind et al. , 2006).…”
Section: Methodsmentioning
confidence: 99%